Total Phenolic Content and Anti-oxidant Capacity of Some Spices and Herbs Grown in Vietnam - Khue, Dang Bui; Tuan, Pham Minh; Quan, Ngo Van; Oanh, Dang Thi Bui (Journal of Postharvest Technology, 2013)
In recent years, the obesity and oxidative stress are the most common factors  affecting the human health. Especially, the rancid foods are plentiful with free  radicals, which trigger chronic diseases such colon cancer, breast cancer, heart  diseases and so on. Therefore, this study focuses on the determination of the  levels and activities of polyphenols extracted from some spices and herbs  applied to traditional Vietnamese foods. The results categorized these plant  materials into 3 sub-categories including one group shows the high total  phenolic content and antioxidative ability (green tea leaves, green guavas and  buffalo spinach leaves). The second group has low total phenolic content, but  high in antioxidant capacity (tungho leaves, onion, elsholtzia leaves, green  mangoes, basil leaves, lemongrass leaves, coriander leaves, green amberella,  turmeric roots, ginger roots, galangal roots) and the last group possessed the  lowest total phenolic content and antioxidant activity (lemon leaves).
Keywords: Herbs; Spice; Total phenolics; Antioxidant activity